تقنين مقياس BSRI باللغة العربية لقياس النوع (Gender) - ماضي, أنجيلا; سالمة, لؤي (Latakia University Journal -Medical Sciences Series, 2018)
This research presents an Arabic version of the Bem Sex-Role Inventory (BSRI), (Bem, 1974) which is a questionnaire to measure gender. Translation and validation procedures followed the steps for trans-cultural validation of psychometric instruments as the five steps advocated by Vallerand (1989). The first step aimed to put a primary version in Arabic. Second step is to test this version. In the third one، the clarity of the version was examined on a sample of 26 people (13 male and 12 female), While in the fourth step، the experimental version was tested after being translated. Last step was to measure the validity and consistency of the version on a sample of 240 people. The results confirm the existing of a short version questionnaire which made up of five factors: three of them measure the Masculinity، while the other two factors measure the Femininity. يقدم هذا البحث نسخة عربية عن مقياس بيم (BSRI : The Bem Sex-Role Inventory ) وهو عبارة عن مقياس لتحديد دور الجنس الذي يسمح بتقييم درجة امتلاك الشخص للصفات الذكورية والانثوية وفقا للمعايير الاجتماعية (Bem 1974). لذلك اتبعنا مجموعة من الإجراءات المتعلقة بالترجمة والمصداقية من خلال تطبيق الخطوات الخمس ذات الصلة بمقاييس نفسية وفروقات ثقافية والمقترحة من قبل Vallerand (1989). هدفت الخطوة الأولى إلى وضع نسخة أولية للمقياس باللغة العربية، ثم تم اختبار هذه النسخة في الخطوة الثانية. في الخطوة الثالثة تأكدنا من وضوح النسخة الأولية للمقياس بتطبيقها على 26 شخصاً (13 ذكراً و13 أنثى)، بينما في الخطوة الرابعة اختبرت النسخة التجريبية المترجمة. في الخطوة الخامسة والأخيرة تم التحقق من صدق وثبات هذه النسخة على 240 شخصاً (200 شخص لاختبار الصدق و40 لاختبار ثبات المقياس). خلص البحث إلى إيجاد نسخة مصغرة للمقياس تألفت من 5 عوامل: ثلاث منها تقيس الصفات الذكورية فيما يقيس العاملان الباقيان الصفات الأنثوية.